(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Vocational schools play a critical role in providing specialized training and education to prepare individuals for specific careers, particularly in technical fields. Specific Background: This research focuses on the implementation of the Creative Problem Solving (CPS) learning model at SMKN 1 Bangil, aiming to assess its impact on student learning achievement in computer-related subjects. Knowledge Gap: While various instructional methods have been explored, there is limited research specifically evaluating the effectiveness of the CPS model in enhancing learning outcomes in vocational education. Aims: The study aims to determine the significant influence of the CPS learning model on student achievement through a quasi-experimental design involving pretest and posttest assessments. Results: The findings demonstrate a notable increase in student performance, with pretest scores averaging 8.76 and posttest scores rising to 11.00, indicating that the CPS model, particularly when supported by video materials, positively impacts learning outcomes. Novelty: This research contributes to the understanding of effective instructional strategies in vocational education by highlighting the efficacy of the CPS model in fostering problem-solving skills. Implications: The results underscore the importance of innovative teaching approaches in vocational training, suggesting that the adoption of the CPS model can enhance student engagement and achievement in technical disciplines. Highlights: • Impact of CPS Model: The implementation of the Creative Problem Solving model significantly enhances student learning outcomes in vocational education. • Assessment Results: A marked improvement in student performance was observed, with pretest scores of 8.76 rising to posttest scores of 11.00. • Innovative Teaching Approaches: The research emphasizes the need for innovative instructional strategies to foster engagement and skill development in technical disciplines. Keywords: Vocational Education, Creative Problem Solving, Student Achievement, Technical Training, Learning Outcomes